CONVERGENCE OF QIBLA DIRECTION ACCURACY OF THE OLD AIR TIRIS GRAND MOSQUE KAMPA RIAU - Novi Arisafitri (Fakultas Syari'ah dan Hukum UIN Walisongo, 2022)
The community experiences both positive and negative consequences as a response of Qibla direction calibration, particularly in the ancient mosque, an ancestral heritage mosque whose authenticity must be preserved. One of them is the Air Tiris Great Mosque in Kampar, which must be preserved from the initial stages of growth because it is a tourist destination and an item of cultural heritage. This article aims to verify the calibration of the Qibla direction of the oldest mosque in Kampar and the techniques employed by earlier scholars in measuring their Qibla direction using field investigations and data sources from observations and interviews. This article concludes that the Qibla direction is accurate and correct, the Air Tiris Grand Mosque was established in 1901, and that it has never undergone renovation. When the global Qibla direction was wrapped in religious intuition, the cleric at the time, Datuk Engku Mudo Songkal, used the sun's shadow to bring religious intuition and scientific truth together.